N-Terminal Fragment of c-FLIP(L) Processed by Caspase 8 Specifically Interacts with TRAF2 and Induces Activation of the NF-κB Signaling Pathway - Kataoka, Takao (American Society for Microbiology, 2004)
Caspase 8 is required not only for death receptor-mediated apoptosis but also for lymphocyte activation in the immune system. FLIP(L), the long-splice form of c-FLIP, is one of the specific substrates for caspase 8, and increased expression of FLIP(L) promotes activation of the NF-κB signaling pathway. The synthetic caspase inhibitor benzyloxycarbonyl-Val-Ala-Asp(OMe)-fluoromethylketone (zVAD-fmk) markedly blocked NF-κB activation induced by overexpression of FLIP(L). FLIP(L) is specifically processed by caspase 8 into N-terminal FLIP(p43) and C-terminal FLIP(p12). Only FLIP(p43) was able to induce NF-κB activation as efficiently as FLIP(L), and FLIP(p43)-induced NF-κB activation became insensitive to zVAD-fmk. In caspase 8-deficient cells, FLIP(p43) provoked NF-κB activation only when procaspase 8 or caspase 8(p43) was complemented. FLIP(p43)-induced NF-κB activation was profoundly blocked by the dominant-negative TRAF2. Moreover, endogenous TRAF2 interacted specifically with FLIP(p43), and the formation of the FLIP(p43)-caspase 8-TRAF2 tertiary complex was a prerequisite to induction of NF-κB activation. zVAD-fmk prevented the recruitment of TRAF2 into the death-inducing signaling complex. Thus, our present results demonstrate that FLIP(p43) processed by caspase 8 specifically interacts with TRAF2 and subsequently induces activation of the NF-κB signaling pathway.